Quantitative organization of GABAergic synapses in the molecular layer of the mouse cerebellar cortex. - Federica Briatore; Annarita Patrizi; Laura Viltono; Marco Sassoè-Pognetto; Peer Wulff (PLoS ONE)
In the cerebellar cortex, interneurons of the molecular layer (stellate and basket cells) provide GABAergic input to Purkinje cells, as well as to each other and possibly to other interneurons. GABAergic inhibition in the molecular layer has mainly been investigated at the interneuron to Purkinje cell synapse. In this study, we used complementary subtractive strategies to quantitatively assess the ratio of GABAergic synapses on Purkinje cell dendrites versus those on interneurons. We generated a mouse model in which the GABAA receptor alpha1 subunit (GABAARalpha1) was selectively removed from Purkinje cells using the Cre/loxP system. Deletion of the alpha1 subunit resulted in a complete loss of GABAAR aggregates from Purkinje cells, allowing us to determine the density of GABAAR clusters in interneurons. In a complementary approach, we determined the density of GABA synapses impinging on Purkinje cells using alpha-dystroglycan as a specific marker of inhibitory postsynaptic sites. Combining these inverse approaches, we found that synapses received by interneurons represent approximately 40% of all GABAergic synapses in the molecular layer. Notably, this proportion was stable during postnatal development, indicating synchronized synaptogenesis. Based on the pure quantity of GABAergic synapses onto interneurons, we propose that mutual inhibition must play an important, yet largely neglected, computational role in the cerebellar cortex.